Exploring Heutagogy in Indonesian Higher Education: Cultural Challenges and Advantages in Mobile-Based English as a Foreign Language (EFL) Teaching - Halim, Abd.; Nur, Sahril; Vega, Nofvia De; Nasta, Mardiyanah; Nurfadhilah, Auliyanti S (Universitas Hamzanwadi, 2023)
This study explores the integration of heutagogy in mobile-based English as a Foreign Language (EFL) teaching within Indonesian higher education, examining its challenges and benefits. Emphasizing learner autonomy, engagement, and motivation, the research employs a qualitative design, involving semi-structured interviews with EFL instructors and students from two Indonesian universities. Thematic analysis reveals cultural barriers to heutagogy, such as traditional teacher-centered methods, hierarchical structures, cultural norms, and language proficiency issues. Despite these challenges, notable advantages include enhanced learner autonomy, engagement, collaboration, communication skills, critical thinking, and the promotion of lifelong learning attitudes. The findings suggest that heutagogical approaches in mobile-based EFL teaching hold promise for Indonesian higher education. The study advocates for the adoption of heutagogical principles, alongside comprehensive training for educators, to foster more learner-centered environments. It also underscores the need for further research to develop strategies to address the challenges and evaluate the long-term effects on student learning outcomes, thereby advancing EFL teaching practices in the region.